Virtual courses for curriculum internationalization: disruptive innovations for higher education teachers - García-Meza, Isabel María (2025)
The virtual impulse of the curriculum internationalization in higher education has increased in recent years due to certain technological innovations. Since internationalization and technology combine in COIL (Collaborative Online International Learning), MOOC (Massive Online Open Courses), and EMI (English-medium instruction) courses, these can imply changes in faculty, their practices, beliefs, and ways of working. Therefore, the objective of this study was to analyze, from an innovation perspective, the effects of implementing virtual courses -COIL, MOOC, EMI- on teaching activity and function, based on the integration of internationalization and technology in teaching. Through a qualitative phenomenological study and cascade sampling, 20 academics who teach these courses at two public universities in northwestern Mexico were interviewed virtually in 2024. The results indicated that these virtual courses are disruptive innovations for faculty, as they have a significant impact on their beliefs and ways of working. While there is a growing openness to collaborative work with ICTs among academics, certain difficulties persist in implementing these virtual courses, as there is a division in the teaching role between teaching, the administration of virtual courses, and the specific demands of the disciplines. Nevertheless, these courses represent important steps toward educational change, internationalization and the use of ICTs are beginning to have an impact on teachers, who are beginning to question their ways of working and teaching.